1992
DOI: 10.1002/hep.1840160110
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic-type biliary complications after orthotopic liver transplantation

Abstract: Nonanastomotic biliary strictures that involve only the biliary tree of the graft occur after orthotopic liver transplantation in patients with hepatic artery thrombosis, chronic ductopenic rejection and ABO blood group incompatibility. This complication may also occur in the absence of these known risk factors. The major focus of our study was to evaluate the risk factors for nonanastomotic biliary stricturing of unknown cause after orthotopic liver transplantation. Results demonstrate that the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
226
2
12

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(253 citation statements)
references
References 17 publications
13
226
2
12
Order By: Relevance
“…[21][22][23][24] In addition, we excluded those patients who developed nonanastomotic strictures within the first 90 days posttransplantation to avoid tainting of the study group with patients having ischemic biliary damage as a result of ischemia/reperfusion-induced injury. 20,25 In a previous article, we showed that ischemic-type biliary strictures occurred at a mean of 82 days following liver transplantation. 20 Moreover, this exclusion is supported by our finding that more than 85% of nonanastomotic strictures in non-PSC patients developed within 90 days posttransplantation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[21][22][23][24] In addition, we excluded those patients who developed nonanastomotic strictures within the first 90 days posttransplantation to avoid tainting of the study group with patients having ischemic biliary damage as a result of ischemia/reperfusion-induced injury. 20,25 In a previous article, we showed that ischemic-type biliary strictures occurred at a mean of 82 days following liver transplantation. 20 Moreover, this exclusion is supported by our finding that more than 85% of nonanastomotic strictures in non-PSC patients developed within 90 days posttransplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the type and duration of graft preservation and the incidence of cytomegalovirus and positive lymphocytotoxic mismatch, previously found to be related to biliary strictures, did not predict PSC recurrence. 25,27 Because the cause of chronic ulcerative colitis and PSC is often considered to be associated with a single immunologic pathophysiologic mechanism, one may speculate that patients with chronic ulcerative colitis may be more prone to experience recurrence of PSC than those without chronic ulcerative colitis. Although the prevalence of chronic ulcerative colitis in the group with suspected recurrent PSC was 92% compared with 76% in the nonrecurrence group, this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] However, the average cold preservation time was approximately 6 hours, and fewer than 10% of the livers were preserved for more than 12 hours. Therefore, adverse effects of prolonged cold ischemia probably would have been minimal in this series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, re oxigenation and warm ischemia time also seem to be involved in the pathogenesis of the disease [27,53]. Moreover, delayed re-arterialization of the graft may favor the occurrence of ITBL [2,43,54]. Therefore, the time period between explantation and reperfusion should be as short as possible under an adequate preserving temperature.…”
Section: Ischemic Timementioning
confidence: 99%